Efektivitas Program Literasi Dalam Meningkatkan Minat Baca Siswa Di SD GMIM Pondang - Sumilat, Juliana M.; Tompunu, Hanna F.; Lumataw, Fernanda A.; Tulenan, Priskila T.; Taareluan, Magdalena Y.; Sarapun, Syalomita Ch.; Merentek, Revalina F. (Peneliti.net, 2025)
This study aims to examine the effectiveness of the Literacy Program in improving students’ reading interest at SD GMIM Pondang. The research employed a case study approach with data collected through classroom observations, documentation, and field notes during the implementation of the morning literacy activities. The findings indicate a noticeable improvement in students’ reading behavior. At the beginning of the program, many students struggled to focus, showed low interest in reading, and often selected books randomly. However, as the activities were carried out routinely, students began to show enthusiasm, develop reading preferences, and become more independent in choosing and completing books. Supporting factors of the program included the availability of varied reading materials, a comfortable reading corner, and consistent teacher guidance. Meanwhile, challenges arose from the limited number of engaging books for all students, differences in reading ability, and classroom environmental distractions. Overall, the Literacy Program proved effective in fostering reading habits and increasing students’ reading interest